MENUMBUHKAN SIKAP PEDULI LINGKUNGAN MELALUI PESAN BERANTAI SEBAGAI UPAYA MEWUJUDKAN SUSTIANABLE DEVELOPMENT GOASL (SDGs) - Ridzal, Dewi Asriani; Haswan, Haswan; Kaif, Sitti Hermayanti; Devi, Sava; Thika , Wa Ode Fandry (Jurnal Abdi Insani, 2025)
Waste constitutes a significant issue encountered by numerous places in Indonesia. The waste issue remains inadequately addressed due to a disparity between the capacity of waste managers and the volume of garbage generated. In addition, the lack of public awareness to manage waste properly is a major obstacle. The Topa Pantai environment is one of the areas in Baubau City that is not free from waste problems. The purpose of this community service activity is to foster an attitude of environmental concern in the community through a chain message program, namely environmental waste management so that it is clean, comfortable, healthy, beautiful, and also beautiful as an effort to realize sustainable development. The activity was carried out in the form of socialization, training, and education in the Topa environment, and the local community (housewives) and students of Topa Elementary School were involved as partners. The activity was carried out through several stages, namely observation to find out partner problems, preparation, and planning of activities, implementation, and evaluation. The socialization and training activities were attended by 15 community partners (mothers), while for Topa Elementary School students, the community service activity was carried out in the form of socialization and education and was attended by 45 students as participants. This activity has had a positive impact on partners in the form of knowledge and skills about waste management. This result can be seen from the evaluation results 1) Partners (housewives) have been able to manage waste well as indicated by the existence of products produced from household waste management such as organic fertilizer from egg shells and crafts from plastic waste; 2) partners (students of Topa Elementary School) have knowledge about waste management where 84% (38 students) have a good understanding and 16% (7 students) also show a fairly good understanding, especially in terms of sorting waste according to type and the impact of waste management. Based on the evaluation results, it was concluded that the implementation of community service activities went well and smoothly in accordance with the objectives that had been set.